Analisis pengaruh bauran pemasaran jasa terhadap keputusan wali murid memilih sekolah dasar - Immanuel Candra irawan (STIE Perbanas Surabaya, 2017)
The increasing participation of the community in basic education makes the student guardian try to compete for the quality of educational institutions for their children so as to create competitive climate for basic educational institutions both public and private status. This research aimed to assess the effect of service marketing mix (product, price, place, promotion, people, physical evidence, and process) on the decision of the guardians of the students in choosing a primary school. The population in this study was all stu-dents of St. Peter Primary School in Nabire, Papua with samples of 180 respondents whose children are in grade 1 to 3. The analysis technique used was descriptive and mul-tiple regression analysis to test the influence of significant service marketing mix both simultaneously and partially to the decision of guardians in choosing a school. Statistical test results show that the service marketing mix together influences the decision of choos-ing a school. Other results show that variables of product, price, place, promotion, people, physical evidence, and process partially significantly affect the school choosing, while price and place variables partially insignificant to the decision of school choosing. Among these variables, promotion is the most dominant variable influencing the decision in choosing a school.